McArdle’s Disease (Glycogen Storage Disease type V): A Clinical Case - T, Calheiros-Cruz; MP, Caamaño-Vara; B, Villar-Fernández; J, Ruibal-Azevedo; L, Cameselle-Cortizo; M, Cameselle-Arias; ME, Charro Gamallo; F, Turienzo-Pacho; A, Yera Acosta; JF, Cameselle-Teijeiro (Archives of Case Reports, 2018)
McArdle’s Disease, or Glycogen Storage Disease Type V, is the result of a deficiency in one of the enzymes responsible for the metabolism of glycogen in the body. Individuals with this disease, lack or produce very small concentrations of the myophosphorylase or glycogen phosphorylase enzyme. McArdle’s disease is a metabolic and recessive genetic disease caused by a mutation on the PYGM gene located on chromosome 11q13. This gene is responsible for the synthesis of the myophosphorylase (or glycogen phosphorylase) enzyme. It is the most common form of muscular glycogenesis. We present here the clinical case of a 35 years old woman diagnosed with McArdle’s disease at the age of 21 after a visit to a Neurologist. It was confirmed that the patient had shown symptoms of this disease at least 10 years before definitive diagnosis: intolerance to exercise, asthenia and muscular weakness. In this report we describe the different signs and symptoms of the disease, as well as the tests performed to confirm the diagnosis by muscle biopsy and genetic analysis. McArdle’s disease is classified as a rare disease and often its diagnosis is delayed due to a lack of knowledge about its symptoms and signs. Our intention is to make, with the description of our clinical case, the information about this disease more available to physicians to prevent future misinterpretations and delayed diagnosis. A medical documentary we have created on “McArdle’s Disease” can be seen in YouTube using the following links: https://youtu.be/HAhoZ7jxz7Q (English version) and https://youtu.be/uZopzSHOl20 (Spanish version).